Exploratory Study of Digoxin Safety Based on Pharmacokinetic Approach and Drug Interactions in Patients with Congestive Heart Failure - Sadli, Nurul Kamilah; Perawati, Santi; Neldi, Vina; Astuti, Novia Tri; Pondawinata, Marizki; Humaira, Syaza Putri (Sciences of Pharmacy, 2026)
Digoxin has a narrow therapeutic index, requiring close monitoring to prevent toxicity, particularly in patients with heart failure, polypharmacy, and impaired renal function. Due to limitations in therapeutic drug monitoring (TDM), we estimated digoxin serum levels using pharmacokinetic formulas based on creatinine clearance. This retrospective observational study aimed to conduct an initial risk screening by estimating digoxin concentrations, evaluating drug interactions, and assessing heart rate in 17 heart failure patients at a regional general hospital in Jambi (January–August 2025). Descriptive analysis revealed that 76% of patients were within the therapeutic range, while 24% exceeded it, with elevated levels correlating with higher creatinine serum and lower creatinine clearance. Common drug interactions involved furosemide, bisoprolol, and proton pump inhibitors, with spironolactone posing a severe risk. Clinically, bisoprolol combined with hypokalemia appeared associated with lower heart rates in patients with predicted toxic concentrations. While the formula-based pharmacokinetic approach serves as a useful exploratory initial screening tool, these findings require further validation through laboratory-based TDM and larger studies.